The impact of the big five personality variables on self-employment survival - Volery, Thierry; Mattes, Jochen (Frontiers in Psychology, 2022)
Based on large, representative Australian household panel, this study investigates to what extent the Big Five personality variables influence self-employment survival and differentiates between successful or unsuccessful exit. In addition, the influence of two moderating variables, tertiary education and the motivation to become self-employed, are considered. Contrary to expectations, we found no impact of the Big Fives variable on self-employment survival in general. In the case of unsuccessful exit, we found that entrepreneurs with a higher level of Conscientiousness tend to stay self-employed although they may not be satisfied with their job. Similarly, entrepreneurs with a tertiary education prolong unsuccessfully self-employment stints, particularly if they exhibit higher level of Emotional Stability. Necessity-driven entrepreneurs exit unsuccessful stints earlier, especially if they exhibit a lower level of Conscientiousness.